2008
DOI: 10.1016/j.clinbiochem.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid measurement of estrogens and their metabolites in human serum by liquid chromatography-tandem mass spectrometry without derivatization

Abstract: This method allows for the simultaneous measurement of four estrogens in human serum within 8 min. It can be routinely employed in a clinical environment and is attractive because of its simplicity in sample processing, micro sample requirement, and high throughput.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 16 publications
0
77
0
2
Order By: Relevance
“…Positive atmospheric pressure chemical ionization and atmospheric pressure photoionization produced a good response for E 2 , but with higher background noise. The LOQs of E 2 assays using positive atmospheric pressure chemical ionization and atmospheric pressure photoionization were comparable with LOQs of assays using negative ESI (30)(31)(32). In this assay, negative ESI was used and in an effort to optimize the ESI response, mobile phase modification was needed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Positive atmospheric pressure chemical ionization and atmospheric pressure photoionization produced a good response for E 2 , but with higher background noise. The LOQs of E 2 assays using positive atmospheric pressure chemical ionization and atmospheric pressure photoionization were comparable with LOQs of assays using negative ESI (30)(31)(32). In this assay, negative ESI was used and in an effort to optimize the ESI response, mobile phase modification was needed.…”
Section: Discussionmentioning
confidence: 94%
“…In this assay, negative ESI was used and in an effort to optimize the ESI response, mobile phase modification was needed. Previous literature showed that adding ammonium hydroxide in the mobile phase could increase the [M-H] − ion intensity (30,31). Ionization suppression, a major concern in the LC-MS/MS method, is a compound-dependent effect and is more severe when operating in ESI, particularly for steroid estrogens (31).…”
Section: Discussionmentioning
confidence: 99%
“…The method used a derivatization procedure to enhance the ionization efficiency, thus allowing uE 3 determination to an LOD of 0.05 ng/mL in serum. Although our method has a higher LOD than other LC-MS/MS methods, mainly because others have used more sensitive LC-MS/MS instrumentation (19,20 ), our method can still meet clinical needs in detecting serum uE 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier published LC-MS/MS methods for estrogens (Anari et al, 2002;Nelson et al, 2004) also lack the sensitivity and the specificity needed to measure low concentrations of estrogens. One of the approaches for enhancing the sensitivity was through the use of negative ion mode ESI on a more sensitive instrument API5000 (Applied Biosystems/ Sciex) (Guo et al, 2008). Additional enhancement in the sensitivity and the specificity for measurement of estrogens was achieved through the use of the derivatization with the use of the derivatization with dansyl chloride-an amine-containing sulfonyl halide (2), in combination with a multidimensional chromatographic separation .…”
Section: Lc-ms/ms In Clinical Diagnosticsmentioning
confidence: 99%